Melioidosis and scrub typhus co-infection in a patient presenting with acute undifferentiated febrile illness - Muhammad Yazli Yuhana; Ampai Tanganuchitcharnchai; Pimpan Sujariyakul; Piengchan Sonthayanon; Kesinee Chotivanich; Daniel H. Paris; Sasithon Pukrittayakamee; Stuart D. Blacksell; Borimas Hanboonkunupakarn (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Melioidosis and scrub typhus are endemic diseases in Malaysia. However, unlike melioidosis, scrub typhus is more difficult to be diagnosed and in Malaysia its true disease burden is unknown. We report a case of severe melioidosis and scrub typhus co-infection in a patient living in a small village in Peninsular Malaysia whom presented with fever and headache. This case highlights the importance of considering scrub typhus as a diagnostic possibility in cases of acute undifferentiated febrile illness in rural areas such as that of in Peninsular Malaysia.